Cognitive performance among older adults with psychotic depression compared to non-psychotic depression. (January 2023) - Vermeulen, Tom; Sabbe, Bernard G.; Østergaard, Søren D.; Giltay, Erik J.; Van der Mast, Roos C.
Highlights: The severity of depressive symptoms appears to be associated with impaired global cognitive functioning, especially attention and executive functioning. The severity of psychotic symptoms appears to be associated with impaired attention and inhibitory control. A dimensional measure of psychotic symptom severity could better inform clinical and academic practice. Abstract: It remains unclear whether psychotic depression (PD) compared to non-psychotic depression (non-PD) among older adults is associated with poorer cognitive performance. For inpatients (60+) with a major depressive episode, cognitive performance in PD and non-PD (categorical) were compared as well as the relationship between symptom severity for depression and psychosis (dimensional) and cognition. Of 90 participants (on average 72.7 years old; range 60–92), 64% were female. The severity of depressive- and psychotic symptoms are both negatively associated with cognitive functioning among older adults with depression. This is of relevance for the treatment of this vulnerable group of patients.